2022
DOI: 10.1093/hr/uhac077
|View full text |Cite
|
Sign up to set email alerts
|

Reporter genes confer new-to-nature ornamental traits in plants

Abstract: This manuscript has been authored by UT-Battelle, LLC under Contract No. DE-AC05-00OR22725 with the U.S. Department of Energy. The United States Government retains and the publisher, by accepting the article for publication, acknowledges that the United States Government retains a non-exclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for United States Government purposes. The Department of Energy will provide public acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…To date, the transformation methods for P. tremula × P. alba 717-1B4 are well-developed and optimized [38][39][40]. In general, it is simple to induce transgenic shoots selected from shoot elongation medium to rooting in root medium in P. tremula × P. alba 717-1B4 transformation [34,35]. In contrast, we found that the rooting rate of P. deltoides WV94 transformation is generally less than 10% under the same condition.…”
Section: Discussionmentioning
confidence: 83%
“…To date, the transformation methods for P. tremula × P. alba 717-1B4 are well-developed and optimized [38][39][40]. In general, it is simple to induce transgenic shoots selected from shoot elongation medium to rooting in root medium in P. tremula × P. alba 717-1B4 transformation [34,35]. In contrast, we found that the rooting rate of P. deltoides WV94 transformation is generally less than 10% under the same condition.…”
Section: Discussionmentioning
confidence: 83%
“…In in vitro gene transformation studies, RUBY is a valuable reporter gene as it did not affect callus induction, plant regeneration, development or fertility of Plukenetia volubilis, Nicotiana benthamiana, and Arabidopsis (Yu et al, 2023). In addition to "in root" gene functional studies, exciting opportunities for creating new horticultural value is achievable in breeding of ornamental plants through RUBY gene expression and heterologous betalain production (Yuan et al, 2022). Single insertion of transgene is the most optimal mode of integration in a transformation assay.…”
Section: Discussionmentioning
confidence: 99%
“…A new reporter RUBY that converts tyrosine to vividly red betalain can be detected without the need of special equipment or chemical treatment [ 99 ]. Another potential reporter for biosensor is eYGFPuv, which has been successfully used as a reporter for plant transformation [ 100 , 101 ]. Both RUBY and eYGFPuv could be used as suitable reporters for building transcriptional- or translational-based biosensors.…”
Section: Next-generation Identification and Design Of Biological Comp...mentioning
confidence: 99%